Can Exercising and Eating Healthy Be Fun and Indulgent Instead of Boring and Depriving? Targeting Mindsets About the Process of Engaging in Healthy Behaviors - Boles, Danielle Z.; DeSousa, Maysa; Turnwald, Bradley P.; Horii, Rina I.; Duarte, Taylor; Zahrt, Octavia H.; Markus, Hazel R.; Crum, Alia J. (Frontiers in Psychology, 2021)
This paper investigates mindsets about the process of health behaviors—the extent to which people associate physical activity and healthy eating with appealing (fun, indulgence) versus unappealing (boring, deprivation) qualities—to promote greater engagement. Study 1 (N=536) examined how mindsets about physical activity and healthy eating relate to current and future health behavior. Study 2 (N=149) intervened in actual fitness classes to compare the effects of brief appeal-focused and health-focused interventions on mindsets about physical activity and class engagement. Study 3 (N=140) designed nutrition education classes that emphasized either the appeal or the importance of fruits and vegetables for health and compared its effects on mindsets about healthy eating and actual fruit and vegetable consumption. Holding more appealing mindsets about health behaviors predicts subsequent physical activity and healthy eating (Study 1). An intervention targeting mindsets about the appeal of physical activity promotes greater participation in fitness classes than emphasizing the importance of meeting activity guidelines (Study 2). Meanwhile, interventions targeting mindsets about the appeal of healthy eating increases fruit and vegetable intake more than emphasizing the importance of eating nutritious foods (Study 3). Taken together, mindsets about the process of health behaviors are influential and changeable factors in motivating physical activity and healthy eating.